Sustainability Implications of Stakeholders’ Perspectives in Agroforestry Management in Manyu Division, South West Region Cameroon. - Njiei, Achu Frida; Mbihbiih, Niying Roger (Advances in Social Sciences Research Journal, 2021)
Agroforestry which focuses on the domestication and cultivation of Non-Traditional Forest Products (NTFP) has important sustainability implications for both livelihoods. Brundtland Report and subsequent international and regional instruments, sustainable development as epitomized in Agenda 2030 of the United Nations Organisation (UNO) has become the cornerstone of developmentalism. This study seeks to examine the interplay of sustainability from a stakeholders’ perspective. The findings of this qualitative method which was conducted in 11 villages in Manyu Division of the South West Region revealed that there was a plethora of stakeholders involved in the domain of agroforestry in the study area. These stakeholders were composed of state institutions (Ministry of Forestry and Wildlife-MINFOF, Program for Sustainable Management of Natural Resources in the South West Region-PSMNR-SWR), international organisations (World Agroforestry Center-ICRAF, the World Wildlife Fund-WWF) and local community based institutions (EFOKHOYU), among others. Agroforestry related programmes implemented by these stakeholders ranged from the creation of training centers, allocation of funds and seedlings to farmers as well as the dissemination of knowledge on land conservation and the development of partnerships among farming communities. The findings revealed that this could be felt at the level of household food security with increased cultivation of species such as Irvingia gabonensis and Irvingia wombulu by nearly 62%. Such high rates of domestication and commercialisation of these species implied that the livelihoods of local farmers were assured without endangering over-exploitation of scarce forest resources. In conclusion, some challenges such as issues related with accessibility, high cost associated with domestication among others complicate the activities of stakeholders in Manyu Division. That notwithstanding, the study recommends that tailor made policy interventions should be deployed to address the challenges raised.